Gypsum treatment in managing the internal phosphorus load from sapropelic sediments; experiments on Lake Laikkalammi, Finland - Salonen, Veli-Pekka; Varjo. Eila; Rantala, Pasi (Finnish Environment Institute et al., 2001)
v ok YHA